Functional outcome of surgical management of Bimalleolar ankle fractures - Santosh Deshpande; Akshay Dudhanale (Asian Journal of Medical Sciences, 2025)
Background: Bimalleolar fractures of the ankle are complex injuries that involve both bone and ligamentous structures, affecting joint stability and function. This prospective study examines the functional outcomes of surgical management for bimalleolar fractures treated at a tertiary care center. Aims and Objectives: This study aims to evaluate the functional outcomes of surgical management in patients with bimalleolar ankle fractures, with a focus on post-surgical complications, recovery rates, and factors influencing prognosis. The primary objectives include assessing post-operative range of motion, the incidence of complications, and overall functional outcomes based on established scoring systems. Materials and Methods: Thirty patients, aged 6–60 years with closed bimalleolar fractures, underwent surgical fixation using various techniques, including malleolar screws, K-wires, and plate fixation. Functional outcomes were assessed over 24 months using clinical evaluations, radiographic analysis, and patient-reported scoring systems. Results: The results showed that 80% of patients achieved good to excellent outcomes, with minimal complications. Complications, such as infection and non-union, were observed in 40% of cases. Conclusion: The findings suggest that surgical management of bimalleolar fractures using internal fixation techniques leads to favorable outcomes, restoring ankle stability and function in most patients. Early intervention, accurate anatomical reduction, and appropriate rehabilitation are essential to optimizing recovery and minimizing complications.